Ca2+ and Ag+ orient low-molecular weight amphiphile self-assembly into "nano-fishnet" fibrillar hydrogels with unusual β-sheet-like raft domains. Issue 3 (23rd December 2022) - Poirier, Alexandre; Le Griel, Patrick; Hoffmann, Ingo; Perez, Javier; Pernot, Petra; Fresnais, Jérôme; Baccile, Niki
Abstract : Calcium or silver ions drive self-assembly of natural glycolipid low-molecular weight gelators (LMWGs) into a fibrillar network hydrogel with a unique "nano-fishnet" structure, characterized by entanglement and β-sheet-like rafts. Abstract : Low-molecular weight gelators (LMWGs) are small molecules ( M w < ∼1 kDa), which form self-assembled fibrillar network (SAFiN) hydrogels in water when triggered by an external stimulus. A great majority of SAFiN gels involve an entangled network of self-assembled fibers, in analogy to a polymer in a good solvent. In some rare cases, a combination of attractive van der Waals and repulsive electrostatic forces drives the formation of bundles with a suprafibrillar hexagonal order. In this work, an unexpected micelle-to-fiber transition is triggered by Ca 2+ or Ag + ions added to a micellar solution of a novel glycolipid surfactant, whereas salt-induced fibrillation is not common for surfactants. The resulting SAFiN, which forms a hydrogel above 0.5 wt%, has a "nano-fishnet" structure, characterized by a fibrous network of both entangled fibers and β-sheet-like rafts, generally observed for silk fibroin, actin hydrogels or mineral imogolite nanotubes, but not known for SAFiNs. The β-sheet-like raft domains are characterized by a combination of cryo-TEM and SAXS and seem to contribute to the stability of glycolipid gels. Furthermore, glycolipid is obtained by fermentation from natural resources (glucose, rapeseed oil), thus showing that naturally engineered compounds can have unprecedented properties, when compared to the wide range of chemically derived amphiphiles.